OPEN-CIRCUIT FAULT DIAGNOSIS IN VOLTAGE SOURCE INVERTER BY PARKS VECTOR APPROACH - Priyanka Ujanikar (International Journal of Innovations in Engineering Research and Technology, 2022)
In this paper, open circuit fault diagnosis is done by normalized parks vector approach. In this method of open-circuit fault diagnosis, parks vector transformation is used to transfer three phase to two phase for easy simplification. This transferred two phase value is further normalized so that become load independent. Further average value and absolute average value of normalized current are used to formulate diagnostic variable. So that normalized Parks Vector approach is robust against false alarm. It detects and localize not only single switch open-circuit fault but also multiple open-circuit fault occur in voltage source inverter.